DESIGNING ICT COMPETENCES-INTEGRATED GRAMMAR ASSESSMENT INSTRUMENTS FOR ENGLISH LANGUAGE STUDY PROGRAM - rinawati pelawi; Sri Sumarni; Darmahusni (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2020)
Technological advancements affect many areas, including education. Proven to bring positive impacts in education, ICT is greatly expected in teaching, learning and assessment. Hence, there is a greater necessity for teachers and lectures to integrate ICT into their teaching, learning, and assessment. This study focuses on the assessment instrument for Grammar course of higher education for English Language Education Study Program. The analysis showed that the ICT Competences integration in the assessment instrument did not reach the levels that are meant for higher education based on standard frameworks UNESCO ICT Competency, EPG and the CEFR. This study aims to design ICT competences-integrated grammar assessment instruments for undergraduate English Language Education Study Program by using standard frameworks UNESCO ICT CFT, EPG and the CEFR. This study adapted Design and Development Research by Peffers. Based on the international standard frameworks, the results of the analyses suggest that the ICT competences of the existing assessment instruments are in the basic phase of EPG and knowledge acquisition level of UNESCO ICT Competency Framework. And the grammatical features are spread from level A2 to C1. Thus, the study proposed a design of ICT Competences-integrated grammar assessment instruments for English Language Education Study Program. Keywords: ICT competence; assessment instruments; UNESCO ICT; EPG.